Screening for natural and derived bio-active compounds in preclinical and clinical studies: one of the frontlines of fighting the coronaviruses pandemic - Khalifa, Shaden A. M.; Yosri, Nermeen; El-Mallah, Mohamed F; Ghonaim, Reem; Guo, Zhiming; Musharraf, Syed Ghulam; Du, Ming; Khatib, Alfi; Xiao, Jianbo; Saeed, Aamer; El-Seedi, Haged H. R.; Zhao, Chao; et al. (Elsevier, 2021)
Background: Starting December 2019, mankind faced an unprecedented enemy, the COVID-19 virus. The world convened in international efforts, experiences and technologies in order to fight the emerging pandemic. Isolation, hygiene measure, diagnosis, and treatment are the most efficient ways of prevention and intervention nowadays. The health organizations and global care systems screened the available resources and offered recommendations of approved and proposed medications. However, the search for a specific selective therapy or vaccine against COVID-19 remains a challenge. Methods: A literature search was performed for the screening of natural and derived bio-active compounds which showed potent antiviral activity against coronaviruses using published articles, patents, clinical trials website (https://clinicaltrials.gov/) and web databases (PubMed, SCI Finder, Science Direct, and Google Scholar). Results: Through the screening for natural products with antiviral activities against different types of the human coronavirus, extracts of Lycoris radiata (L’H´er.), Gentiana scabra Bunge, Dioscorea batatas Decne., Cassia tora L., Taxillus chinensis (DC.), Cibotium barometz L. and Echinacea purpurea L. showed a promising effect against SARS-CoV. Out of the listed compound Lycorine, emetine dihydrochloride hydrate, pristimerin, harmine, conessine, berbamine, 4`-hydroxychalcone, papaverine, mycophenolic acid, mycophenolate mofetil, monensin sodium, cycloheximide, oligomycin and valinomycin show potent activity against human coronaviruses. Additionally, it is worth noting that some compounds have already moved into clinical trials for their activity against COVID-19 including fingolimod, methylprednisolone, chloroquine, tetrandrine and tocilizumab. Conclusion: Natural compounds and their derivatives could be used for developing potent therapeutics with significant activity against SARS-COV-2, providing a promising frontline in the fighting against COVID-19.